(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2022)
The article is devoted to identifying the system of subjects of intellectual property law in the conditions of the formation of cyberspace. The topic of the article covers the subject composition of intellectual property legal relations. The purpose of the article is to define the system of subjects of intellectual property law, taking into account the virtual and digital aspect. The research methodology consisted of a system of general scientific and special methods of scientific knowledge. The application of the dialectical method has made it possible to establish that digital law is developing as a complex institution that gravitates towards private law. Thanks to the use of the formal legal method, it has been stated that the author and co-authors have the right to create their own virtual identity in the digital environment, which can be the object of intellectual property legal relations, in particular copyright. Based on the application of methods of analysis and synthesis, it has been determined that modern subjects of intellectual property law are divided into primary, derivative and auxiliary. It has been proven that the development of cyberspace has a direct impact on the formation of new subjects of intellectual property law. The author in cyberspace has the right to: create their own virtual identity, which will be the object of intellectual property legal relations; to place their own results of creative, scientific, intellectual work. Derivative subjects of intellectual property rights are persons who acquire property rights to the already created, existing result of creative, intellectual, scientific work in a material and/or virtual environment. Auxiliary subjects of intellectual property law perform an auxiliary function regarding the implementation of state intellectual property policy, creation of an object of intellectual property law, registration of property rights to these objects, stimulation of creative activity, and more. The results of the article can be used in scientific works in the field of intellectual property law, as well as by lawyers when identifying the subject structure of intellectual property legal relations. It has been concluded that there is an actual problem of identification of the virtual author, the relationship of virtual identity with a real person, the place of digital law research in the legal system, in particular, it is proposed to determine it by the institute of intellectual property law.